Drilling holes in Mars. - Zorpette, G. (IEEE spectrum)
This paper describes an electric drill that will make the first holes in rocks on Mars. Attached to a robotic arm on the mission's roving vehicle, the Rover Rock Abrasion Tool will bore holes 45 mm in diameter and 5 mm deep in Mars rocks. To make each indentation, Honeybee has been allotted only 32.5 Wh. The drill itself with its diamond bit weighs just 0.7 kg